The Relationship of Formula Milk Promotion with The Intention of Exclusive Breast Milk in Babies Aged 0-6 Months in The Work Area of The Tering Health Center West Kutai District in 2022 - Sukensi, Sukensi; Hilda, Hilda; Ariefah Putri, Rosalin (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Breast milk is an ideal nutrition for babies which contains the most suitable nutrients for the baby's needs and contains a set of protective substances to fight disease. The success of exclusive breastfeeding is influenced by a mother's intention to give exclusive breastfeeding, but currently the influence of formula milk promotion is very large and affects the coverage of exclusive breastfeeding. Objective: to determine the relationship between promotion of formula milk and the intention of exclusive breastfeeding in infants aged 0-6 months.  Methods: This type of research is descriptive analytic with a cross sectional design. Result and Discussion: There is a relationship between the promotion of formula milk and the mother's intention to provide exclusive breastfeeding to infants aged 0-6 months in the Working Area of ??the Tering Public Health Center in West Kutai Regency in 2022 with a p value of 0.000 and OR = 28.500. Promotion of formula milk that is carried out on a large scale can affect the mother's intention to give exclusive breastfeeding because the promotion of formula milk gives a wrong understanding that formula milk is as good as exclusive breastfeeding.  Conclusion: promotion of formula milk can affect the intention of exclusive breastfeeding in infants aged 0-6 months